THE SPATIAL STUDY OF HEALTH CONDITION OF SOCIETY TOWARDS INCOME GRADE IN PRAMBANAN, KLATEN REGENCY - Ayu Fatonah; Fitria Febri Setiyani; Hafiz Winardany; S Samidu; Bagas Anindra Murdiansyah; Fitri Nur Aini (Department of Geography Education, University of Jember, 2018)
Health is the most important aspect of the human being life. A good health will affect other aspects, one of which will affect the economic aspect of the income earned by individuals. The purpose of this research is to know the correlation between health condition and income of society in Prambanan Sub-district. This research uses quantitative descriptive research, with the research variables such as health data and income data. The sample in this study amounted to 2,235 respondents from 16 Villages in Prambanan Sub-district, Klaten. The Data Collection Method used in this research are interview, observation and questionnaire with the data analysis technique is quantitative descriptive analysis which is non statistical analysis with frequency table. The results show that there is not a significant correlation between health and income. Pereng Village has an average of